A process for the preparation of an alcohol-soluble modified polyamide resin

CN117683229BActive Publication Date: 2026-10-30SHANDONG FIRST MEDICAL UNIV & SHANDONG ACADEMY OF MEDICAL SCI
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202311210352.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2026-10-30
Estimated Expiration
2043-09-19

AI Technical Summary

Benefits of technology

[0055]1、使用二聚酸含量为80%左右的工业二聚酸,不使用高纯度的工业二聚酸(二聚酸含量为98%),通过改变不同的有机酸种类、不同的有机胺种类,调整各种有机酸和有机胺的用量,合理调整合成工艺,制备了熔点、冻点等各个质量指标合格的改性聚酰胺树脂,生产工艺稳定,操作简便。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a preparation method of an alcohol-soluble modified polyamide resin, which is prepared by reacting organic acids and amine compounds. The organic acids include industrial dipolymer acid, isophthalic acid diethylene glycol ester-5-sulfonic acid lithium, industrial acetic acid, isobutyric acid, ricinoleic acid and suberic acid. The amine compounds include ethylenediamine, hexahydrated piperazine, decanediamine and triethanolamine. The molar ratio of the organic acids to the amine compounds is 1:1.05-1.2, and the amine compounds are excessive. The preparation method provided by the application shortens the reaction time by nearly 2 hours compared with the common production process, and lowers the reaction temperature by 10 DEG C compared with the common production process. The product storage stability is improved, and the gel recovery time is short.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyamide preparation technology, specifically to a method for preparing alcohol-soluble modified polyamide resin. Background Technology

[0002] Polyamide resins are typically obtained through the condensation polymerization of diacids and diamines. As a high-performance and widely used chemical raw material, they exhibit good chemical resistance, resisting acids, alkalis, and vegetable and mineral oils. Their softening point range is particularly narrow; they cure rapidly when the temperature is slightly below their melting point, unlike other thermoplastic resins which undergo a gradual curing or softening process. Based on their properties, they can be divided into two main categories: non-reactive or neutral polyamide resins and reactive polyamide resins. Reactive polyamide resins are used as curing agents in epoxy resins and in thermosetting surface coatings, adhesives, lining materials, and canning and molding resins. Neutral polyamide resins are obtained through the stepwise condensation polymerization of dimer fatty acids and amine compounds. They possess good flexibility and adhesion, as well as a suitable softening point, and are used in the production of inks, hot melt adhesives, and coatings. The polyamide resins used in the ink industry and those used in the chemical fiber industry have completely different performance requirements. Printing inks are mainly made by grinding and filtering polyamide resins and other binders, along with pigments and additives. The polyamide resins used are broadly divided into two categories: benzene-soluble polyamide resins, mainly used in surface gravure inks, and alcohol-soluble polyamide resins. However, the alcohol solubility of polyamide resins currently supplied by domestic manufacturers is poor, requiring the addition of a certain amount of aromatic solvents to improve their solubility. Furthermore, they may freeze at certain temperatures. In China, over 95% of plastic flexible packaging printing uses gravure printing. The softening point of polyamide resin must be controlled between 121-123℃; otherwise, due to the low softening point, printed materials may stick together during the rainy season. If the softening point is high, freezing may occur during winter use, requiring heating and mixing to melt it. During production and use, strong solvents such as toluene and other aromatic solvents are needed to dissolve and adjust the viscosity of the ink.

[0003] In their paper "Performance Study of Dimeric Acid-Based Alcohol-Soluble Polyamide Resins for High Freeze-Resistant Inks" published in the March 2009 issue of "Forest Products Chemistry and Industry", Huang Kun, Xia Jianling, Li Mei, and others synthesized a series of polyamide resins for inks with good freeze-resistance using monomers such as dimer acids and isophorone diamine (IPDA) via melt polycondensation. The freezing point of the 20% n-propanol solution reached -35℃. Although the freezing point decreased, the softening point increased, and the solubility of polyamide resin in ethanol could not be improved; it could only be dissolved in n-propanol, tetrahydrofuran, and n-butyl acetate. Gao Jianzhou, Wang Cundong, and Wang Haixia published a paper titled "Synthesis and Performance Study of Dimer Acid-Type Polyamide Hot Melt Adhesive" in the November 2015 issue of *Chinese Adhesives*, investigating the effects of piperazine and dimer acid dosage on the performance of dimer acid-type polyamide HMA (hot melt adhesive), but still failing to solve the problems of high glass transition temperature and decreased softening point. Chinese invention patent CN1353128 discloses a method for preparing polyamide resin for alcohol-soluble inks. This method involves adding isophthalic acid sulfonate as a modifier to the reaction system of dimer acid and ethylenediamine to prepare alcohol-soluble polyamide resin. However, alcohol-soluble polyamide resins have poor mechanical properties, limiting their applications and confining them to general ink resins. Chinese invention patent CN104893406 discloses a method for producing alcohol-soluble polyamide resins. This method involves weighing dimer acid, monoacid, and ethylenediamine and placing them in a reaction vessel. A vacuum pump is used to evacuate the vessel to a pressure of 2.5 MPa, followed by a condensation reaction for 45 minutes to obtain the alcohol-soluble polyamide resin. The alcohol-soluble polyamide resin is then mixed with an alcohol solvent at a weight ratio of 2:8 to obtain an alcohol-soluble mixed solvent. The drawback is the relatively high reaction pressure and poor safety performance. Gao Jin, Hu Zhongxin, Yang Cuilian, et al. published a paper titled "Synthesis and Performance Study of Alcohol-Soluble Polyamide Resin for Ink" in the February 2012 issue of the *Journal of Zaozhuang University*, exploring the effects of the ratio of monoacid and amine components, polymerization temperature, and polymerization time on the synthesized polyamide resin. However, the overall performance of the prepared resin did not show a breakthrough improvement.

[0004] In recent years, representative Chinese patents such as CN1098875C, CN108912326A, CN103554485A, CN103554486B, CN115260488A, CN00100075.6, CN101613472B, CN103113577A, CN108047387A, CN107652431A, CN202210638268.2, and CN104788671A have modified polyamide resins in many ways. Extensive research and exploration have been conducted on improving the hardness and transparency of polyamide resins, adjusting the softening point, adjusting the viscosity, improving the freezing point, regulating weather resistance, altering heat stability, and improving electrical properties. However, the quality of domestically produced alcohol-soluble resins still has some shortcomings, such as darker color, poor transparency, severe gelation tendency, poor gel recovery, and poor solubility in pure alcohol solvents. Summary of the Invention

[0005] The current challenge in polyamide synthesis lies in simultaneously improving its alcohol solubility and anti-gelling properties. To overcome the shortcomings of existing technologies, this invention provides a method for preparing alcohol-soluble modified polyamide resins. Starting with the molecular structure of polyamides, this invention utilizes the principle of "like dissolves like" to increase the polarity of the monomers used in the synthesis of polyamides or adds some solubilizing polyamide resins. By altering the polyamide structural sequence and molecular chain topology, an alcohol-soluble polyamide resin suitable for plastic printing is developed. The modified polyamide resin obtained by this invention exhibits improved overall performance and also addresses some existing quality deficiencies, such as darker color, poor transparency, low gloss, and severe gelation tendency.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing an alcohol-soluble modified polyamide resin involves reacting an organic acid with an amine compound. The organic acid includes industrial-grade dimer acid, lithium diethylene glycol 5-sulfonate isophthalate, industrial-grade acetic acid, isobutyric acid, ricinoleic acid, and octanoic acid. The amine compound includes ethylenediamine, piperazine, decanediamine, and triethanolamine. The molar ratio of the organic acid to the amine compound is 1:1.05-1.2, with the amine compound in excess.

[0008] Preferably, the molar ratio of industrial dimer acid, lithium diethylene glycol isophthalate-5-sulfonate, industrial acetic acid, isobutyric acid, ricinoleic acid, and octanoic acid in the organic acid is 1:0.15-0.36:0.15-0.25:0.15-0.32:0.15-0.28:0.05-0.18.

[0009] Furthermore, the industrial-grade dimer acid contains 80-85% dimer acid, ≤15% trimer acid and other polyacids, and ≤5% monoacids, other fatty acids, and other impurities.

[0010] Preferably, the molar ratio of ethylenediamine, piperazine, decanediamine and triethanolamine in the amine compound is 1:0.15-1:0.02-0.25:0.15-0.27.

[0011] In embodiments of the present invention, piperazine is added in the form of piperazine hexahydrate.

[0012] Furthermore, the preparation method uses phenylphosphine as a catalyst, and the amount added is 0.003%-0.02% of the mass of the industrial grade dimer acid.

[0013] Furthermore, the preparation method uses tetrabutyl titanate as a catalyst, and the amount added is 0.008%-0.06% of the mass of industrial grade dimer acid.

[0014] Using the method provided by this invention, the molecular structure of the modified polyamide resin is different from that of the existing products, mainly in the structure of the copolymer and the arrangement order of the different polymers.

[0015] Among the various properties of polyamide resins, alcohol solubility and gel recovery are the most important. Gel recovery refers to the fact that when resin alcohol solutions or inks are used, stored or transported, especially in cold climates, they often coagulate into gels. The gel state is not suitable for printing, so we want the ink to be less likely to gel, and once it has gelled, we want it to be easy to degel. This ability to degel is generally called gel recovery.

[0016] Dimer acids, as a major raw material for the production of polyamide resins, possess a relatively long nonpolar hydrocarbon group, which can improve the compatibility and wettability of the resin with polyolefin materials. Polyamide resins prepared using dimer acids exhibit outstanding water resistance and flexibility. Among all dicarboxylic acids, dimer acids have the most unique molecular structure, with a relatively long main chain containing 36 carbon atoms and two large alkyl branches. Depending on the raw materials, they contain various isomers such as acyclic, monocyclic, and bicyclic, and are entirely derived from biomass conversion.

[0017] In this invention, lithium diethylene glycol 5-sulfonate is used as a modifier, which has the advantages of significantly improving the alcohol solubility of the resin, improving the color of the resin after cooling, improving the storage stability of the resin, and increasing the storage stability of the resin solution.

[0018] In this invention, industrial acetic acid is used as a molecular weight regulator. By controlling its dosage, resins with specific molecular weights can be prepared. Lower molecular weights result in better alcohol solubility but poorer film-forming properties. The addition of industrial acetic acid can adjust the chain length during polycondensation.

[0019] In this invention, isobutyric acid acts as an acid modifier. Isobutyric acid is an isomer of n-butyric acid, and its end-capping function improves the freezing point of dimer acid-type polyamide ink resin solutions. The effect of isobutyric acid on low-temperature performance is mainly due to its improved molecular structure symmetry. Generally, the more branches on the chain, the worse the molecular symmetry, the weaker the van der Waals forces between molecules, the less compact the molecular packing, and the lower the freezing point. The position of the branches has a significant impact on the reduction of the freezing point. Studies have shown that the effect of branch position on the freezing point generally follows a rule of greater reduction in the middle and smaller reduction at both ends; that is, the closer the branch is to the middle, the greater the reduction in freezing point, and the closer or farther away from the carboxyl group, the smaller the reduction. The carbon chain length of the branches also affects the reduction of the freezing point, but to a lesser extent than the effect of their position. Generally, for molecules of the same molecular weight, the longer the branch, the greater the reduction in freezing point.

[0020] Castor oil acid acts as an acid modifier. Adding a small amount of castor oil acid as a chain terminator during the polycondensation reaction allows it to react with terminal amine groups to form amide groups, effectively controlling the average molecular weight of the polyamide resin. Furthermore, the addition of castor oil acid reduces hydrogen bonds and crosslinking that naturally exist between adjacent amide chains, thereby improving the solubility and solution stability of the modified polyamide in alcohol solvents. Additionally, castor oil acid introduces hydroxyl groups into the polyamide molecular chain, imparting alcohol solubility to the modified polyamide resin.

[0021] Octyl succinic acid acts as an acid modifier. Adding appropriate amounts of octyl succinic acid can improve the softening point, molecular chain flexibility, and antifreeze effect of polyamide resins. However, once the amount of octyl succinic acid reaches a certain proportion, while the antifreeze effect increases with increasing octyl succinic acid dosage, the softening point decreases, the resin feels soft, and it is prone to sticking after ink production. Therefore, the amount of octyl succinic acid added must be controlled. The molar ratio of dimer acid to octyl succinic acid can significantly change the softening point. Studies have shown that as the amount of octyl succinic acid decreases, the softening point of the resulting polyamide resin decreases. This is because: as the molar ratio of dimer acid to sebacic acid increases, the density of amide groups in the resulting polyamide resin decreases, reducing the probability of hydrogen bonding and thus the intermolecular forces, thereby decreasing the resin's softening point; as the amount of octyl succinic acid increases, the ratio of amide groups to methylene groups in the resin increases, thus increasing the resin's softening point. Therefore, increasing the amount of octyl succinic acid can produce resins with higher softening points.

[0022] Piperazine hexahydrate acts as an amine modifier and a low-temperature performance regulator. Piperazine-containing dimer acid polyamide resins have a wide softening temperature range, good adhesion to vinyl polymers, and are easily softened. The dimer acid polyamide resins synthesized with piperazine introduce secondary diamine segments into the molecule. Due to the lack of hydrogen atoms on the nitrogen atom, the formation of hydrogen bonds in the system is somewhat hindered, thus affecting the strength, elongation, viscosity, and glass transition temperature of the polyamide. In the structure of dimer acid polyamide hot melt resins, long-chain aliphatic groups are more mobile than aromatic or aliphatic groups. The migration and recrystallization of long-chain aliphatic groups increases the ratio of hydrogen bonds formed between amides in the polyamide molecule. Therefore, over time, the crystal lattice of the polyamide resin tends to become more regular, leading to decreased flexibility and increased brittleness. Piperazine-containing dimer acid polyamide resins have a wide softening temperature range, good adhesion to vinyl polymers, and are easily softened.

[0023] Decadediamine is an amine modifier. In synthetic systems involving decanediamine and ethylenediamine, the softening point of the resulting polyamide resin gradually decreases with increasing decanediamine mass, and the viscosity of a 40% concentration solution also shows a decreasing trend. This is because the reduced amide bond density in the polyamide chain containing decanediamine is unfavorable for the formation of hydrogen bonds between polyamide macromolecules and the crystallization of polyamide, thus leading to a decrease in the softening point with increasing decanediamine mass. When the molar ratio of ethylenediamine to decanediamine reaches a suitable value, the performance of the polyamide resin meets the requirements of printing ink binder resins.

[0024] According to relevant information, adding a certain amount of long-chain diamines during polyamide synthesis helps improve resin solubility and lower freezing point. However, the increase in the carbon chain length of the diamine will lower the resin's softening point.

[0025] Triethanolamine acts as an amine modifier and is used as an alcohol-solubilizing agent. Adding a certain proportion of monoamine to a diamine can improve the alcohol solubility of polyamide resins and enhance their miscibility with other resins. Triethanolamine's molecular structure contains hydroxyl (-OH) groups; adding triethanolamine introduces hydroxyl groups onto the polyamide resin chain, thus modifying the polyamide resin and increasing its alcohol solubility. Simultaneously, it introduces side chains into the main chain, increasing the distance between molecular chains and improving the resin's stability in alcohol solvents. Studies have found that when the molar equivalent of triethanolamine is low, the synthesized resin exhibits poor low-temperature stability and a high freezing point. The alcohol solubility also decreases accordingly. At higher molar equivalents, gelation occurs in the product.

[0026] The present invention uses phenylphosphine as a catalyst, which accelerates the amidation reaction and also acts as a stabilizer in the polycondensation reaction.

[0027] This invention uses tetrabutyl titanate as a catalyst. In the later stage of the polycondensation reaction, the viscosity of the material increases, making it difficult for small molecules to diffuse in the melt. To obtain high molecular weight copolyester, it is necessary to stay in the polycondensation reactor for a long time, which will lead to degradation reaction, causing the resin to turn yellow and produce thermal decomposition products, thus reducing the performance of the product. This invention shortens the polycondensation reaction time by using tetrabutyl titanate and meets environmental protection requirements.

[0028] This invention utilizes molecular weight regulators and various modifiers (including acidic and amine modifiers) to improve the freeze resistance and alcohol solubility of polyamide resins. However, freeze resistance and anti-blocking properties are somewhat contradictory, especially since the addition of some modifiers can significantly lower the softening point. Generally, a too-low softening point makes the resin prone to stickiness.

[0029] This invention reveals that the quality control of industrial-grade dimer acid, the main raw material, has a significant impact on product quality. Industrial-grade dimer acid is a dicarboxylic acid composed of unsaturated fatty acids or unsaturated fatty acid esters that bond through intermolecular interactions, forming C-C bonds, or linked in monocyclic or bicyclic forms. It is a complex mixture containing various isomers, primarily dimer acid, along with trimer acid and its polymers, and unpolymerized monomeric acids. The viscosity of dimer acid is related to the component content; a decrease in viscosity and an increase in monomeric acid content lead to a decrease in the molecular weight and softening point of the synthesized resin. Conversely, an increase in trimer content results in poorer alcohol solubility of the resin due to cross-linking.

[0030] Because polyamide resin is synthesized at high temperatures, and industrial dimer acids contain a certain amount of trimer or polyacids, the oxidation during the synthesis process can lead to excessively dark colors, which has a significant impact on the manufacture of light-colored inks or inks requiring light colors.

[0031] The composition of dimer acids is complex. Excessive monoacid content results in a low molecular weight of the polyamide resin, leading to significant brittleness, poor flexibility, and difficulty in improving adhesive strength. Conversely, excessive trimer content leads to easy cross-linking during polymerization, excessively high molecular weight, poor resin thermal stability, and a tendency to agglomerate and gel upon heating. Therefore, the preparation and purification of dimer acids are crucial. Different grades of dimer acids can be selected based on the required physicochemical properties of the polyamide resin and cost affordability. In production, the viscosity method is typically used to select and control the dimer acid content. Too low a viscosity indicates a high monoacid content; too high a viscosity indicates an excessive trimer content. The dimer acid selected in this invention meets the requirements for synthesizing the target product.

[0032] The selection criteria for fatty acids to participate in the reaction are as follows:

[0033] The research results show that: (1) Linear or nonlinear monocarboxylic fatty acids can be used, especially nonlinear monocarboxylic fatty acids, which can not only play a chain termination role, but also have an anti-gelling effect. It is reported that the anti-gelling effect of the resin is improved by increasing the content of branched fatty acids; (2) Fatty acids containing hydroxyl groups can effectively increase the alcohol solubility of the resin due to the introduction of the functional hydroxyl groups; (3) Compared with the resin made by saturated diacids, polyamide resins made by diamines and unsaturated diacids are more soluble in organic solvents. The modified acids used above should generally have functional groups, branched chains, contain double bonds, and have carbon chain lengths that are much shorter than those of dimer acids, thereby increasing the softening point of the resin.

[0034] The selection criteria for organic amine compounds participating in the reaction are as follows:

[0035] According to relevant information, adding a certain amount of long-chain diamine (decanediamine) in polyamide synthesis helps improve resin solubility and lower freezing point. Adding a certain proportion of monoamine to the diamine can improve the alcohol solubility of polyamide resin and its miscibility with other resins. Adding aliphatic amines containing hydroxyl groups can introduce hydroxyl groups into the polyamide resin chain, thus modifying the polyamide resin to improve alcohol solubility. However, the increase in the carbon chain of the diamine will lower the resin's softening point. If the proportion of ethylenediamine in the mixed diamine is too high after adding other amine modifiers, the prepared resin will be brittle, reducing the adhesion of the printed film and making it prone to peeling. Introducing alicyclic monomeric amines can improve the antifreeze properties of the polyamide resin solution.

[0036] The material ratio affects the performance indicators of polyamide resin:

[0037] By changing the composition and ratio of raw materials, dibasic acid polyamide resins with different physicochemical properties can be obtained. In the formulation of polyamide resins, increasing the amount of dibasic acid can increase the melting point of the resin; if a long-chain diamine is used in the diamine, the toughness of the resin increases and its flexibility is better. However, regardless of how the composition and ratio of raw materials are changed, the equivalent ratio of acid to amine remains basically unchanged.

[0038] The ratio of dimer acid to monoacid is a major factor affecting the softening point. Therefore, when introducing long-chain diamines, the ratio of monoacids must be adjusted appropriately; insufficient addition of monoacids or incomplete mixing with the dimer acid will cause difficulties in resin dissolution. Octadectocarbon monoacids in dimer acids (the content of octadecanoic monoacids in dimer acids is generally 5%-10%) function similarly to chain terminators, but an increase in carbon chain length affects the resin's softening and freezing points. In the formulation of reactants, we prefer that the chain terminator have a short carbon chain. If the content of monomeric acid in the dimer acid is too high, the amount of chain terminator added during resin preparation must be limited, resulting in a low softening point, a high freezing point, and frequent turbidity in the resin solution.

[0039] The softening point of polyamide resins is related to the selected diacid and diamine. As the hydrocarbon chain length increases, the polymer softening point decreases, while the solubility increases. Among diamines, primary diamines produce products with higher softening points than secondary diamines, and they are also more readily reacted.

[0040] The gel time of polyamide resin solutions decreases as the concentration increases; at the same concentration, the longer the carbon backbone, the longer the gel time.

[0041] The preparation method provided by this invention includes the following steps:

[0042] Step 1, Feeding: Add organic acid and catalyst phenylphosphine to the reactor and stir. Use vacuum to draw amine compounds into the reactor from the bottom. After feeding is complete, introduce nitrogen gas. When the pressure gauge of the reactor shows a slight positive pressure, vent the gas and turn off the nitrogen gas.

[0043] Step 2, amidation reaction: After all materials have been added, heat the mixture to react.

[0044] Step 3, Polycondensation reaction: Add the catalyst tetrabutyl titanate to the reactor all at once, and continue to heat the reactor for further reaction;

[0045] Step 4: Filter and discharge.

[0046] Preferably, the amidation reaction in step 2 adopts a gradient temperature program. After all materials are added, the reactor is heated for 0.5 to 1 hour after stirring. The temperature inside the reactor is raised to 100°C to 110°C within 15 to 25 minutes and maintained for 1 to 1.5 hours. Then the temperature inside the reactor is raised to 130°C to 150°C and maintained for 1 to 1.5 hours.

[0047] Preferably, in step 3, the polycondensation reaction adopts a gradient temperature program. The catalyst tetrabutyl titanate is added to the reactor all at once, and the temperature is continued to rise to 180°C to 200°C within 20 to 30 minutes. After holding for 1.5 to 2 hours, the temperature is raised again to 220°C to 230°C within 10 to 20 minutes and held for 0.5 to 1 hour. The temperature is then maintained within the range of 220°C to 230°C.

[0048] Specifically, the preparation method provided by this invention includes the following steps:

[0049] Step 1, Feeding: Weigh the industrial dimer acid, lithium diethylene glycol isophthalate-5-sulfonate, industrial acetic acid, isobutyric acid, ricinoleic acid, octanoic acid, and catalyst phenylphosphine acid into the reactor through the feed port on the top cover. Turn on the reactor stirring. Weigh the ethylenediamine, decanediamine, triethanolamine, and piperazine hexahydrate solution dissolved in hot water into the reactor through the discharge port at the bottom of the reactor in sequence using vacuum suction. After the suction is completed, close the discharge port valve, then open the feed port valve on the top cover of the reactor and introduce nitrogen gas. When the pressure gauge of the reactor shows a slight positive pressure, vent the gas. Repeat the venting process three times and close the nitrogen cylinder outlet valve.

[0050] Step 2, amidation reaction: After all materials have been added, stir for 0.5 to 1 hour and then start heating the reactor. Raise the temperature inside the reactor to 100℃ to 110℃ within 15 to 25 minutes and maintain it for 1 to 1.5 hours. Then raise the temperature inside the reactor to 130℃ to 150℃ and maintain it for 1 to 1.5 hours. At this time, observe that the water flowing out of the sight glass changes from a thin stream to droplets, and the amount of droplets becomes less and less until almost no water droplets appear. Measure the amount of water released from the water receiver. If the amount of water reaches 90% of the theoretically calculated value, it indicates that the amidation reaction has ended.

[0051] Step 3, Polycondensation Reaction: Add the catalyst tetrabutyl titanate to the reactor all at once, continue heating, raise the temperature to 180℃~200℃ within 20~30 minutes, maintain it for 1.5~2 hours, raise the temperature again, raise the temperature inside the reactor to 220℃~230℃ within 10~20 minutes, maintain it for 0.5~1 hour; after maintaining the temperature within the range of 220℃~230℃, take a sample from the bottom discharge port of the reactor for analysis of amine value and acid value. If both are qualified, vacuum the reactor and start the vacuum unit according to the standard operation. Start timing from when the absolute pressure inside the reactor reaches 150Pa, and vacuum the reactor for 0.5~1 hour. During this process, maintain the temperature inside the reactor at 220℃~230℃.

[0052] Step 4, Filtration and Discharge: After vacuuming, nitrogen is used to press the material from the reactor into a precision filter with an insulated jacket for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen, cooled to 160°C, discharged, and the finished product is obtained. Samples are taken for analysis.

[0053] In step 2, the amidation reaction, the acid and amine undergo amidation at the first temperature, and at the second temperature, some of the water generated in the reaction and the water used to dissolve the piperazine are distilled off. The reaction is divided into two stages: the first stage is the salt formation of the amide, which is relatively fast; the second stage is the polymerization of the amide salt into polyamide resin, which is slower and requires a higher temperature and a longer reaction time. To produce high-quality polyamide resin, besides the process formulation, controlling the reaction conditions is crucial. The completeness of the salt formation stage is critical to the final quality of the polyamide resin. A suitable reaction temperature must be selected and determined during the salt formation stage. If the reaction temperature is too high, polymerization will occur simultaneously with salt formation, resulting in resins with significantly different molecular weights and unstable final product quality.

[0054] Compared with the prior art, the beneficial effects of the present invention are:

[0055] 1. Using industrial dimer acid with a dimer acid content of about 80%, instead of high-purity industrial dimer acid (dimer acid content of 98%), modified polyamide resin with qualified melting point, freezing point and other quality indicators was prepared by changing different types of organic acids and organic amines, adjusting the dosage of various organic acids and organic amines, and reasonably adjusting the synthesis process. The production process is stable and easy to operate.

[0056] 2. By selecting appropriate materials and adjusting the formula, adding branched isobutyric acid, ricinoleic acid with hydroxyl groups, succinic acid with two carboxyl groups, cyclic secondary amine piperazine, and triethanolamine with hydroxyl groups, the prepared product exhibits significantly better anti-gel properties and other properties than products prepared using existing processes for the same purpose. The raw material composition ratio and preparation method are scientifically sound, and the amidation reaction temperature and time can be effectively controlled during the preparation process, with gradient heating ensuring uniform reaction. Moisture and unreacted low-boiling-point organic amines in the product are effectively removed, resulting in minimal residue that does not affect the quality and use of the final product. The product's effective performance is stable.

[0057] 3. The use of a screw-ribbon combined agitator enhances the heat and mass transfer of reactants, resulting in faster reaction speeds, better reaction effects, and shorter reaction times and production operation cycles. Compared to the frame or anchor agitators currently used in the industry, the frame agitator, similar to the anchor agitator but with the addition of a horizontal blade, offers increased rigidity and mixing force. Its vertical blades remain parallel and close to the inner wall of the reactor, facilitating the scraping of deposited materials and improving thermal conductivity. The screw-ribbon agitator, primarily composed of a screw and ribbon combination, provides excellent mass and heat transfer and mixing uniformity, combining the advantages of both. While its structure is relatively complex, it is suitable for reactions involving high-viscosity fluids. The excellent stirring effect helps to uniformly disperse various reactants in a high-viscosity environment, preventing potential localized agglomeration.

[0058] 4. A unique raw material and formulation were researched and designed using a screw-ribbon combined agitator, and the reaction was carried out by direct feeding of raw materials. The feeding method of organic amine raw materials was changed from the dropwise amine addition method currently favored and focused on in the industry to a mixed amine addition method, that is, all raw materials participating in the reaction (including all organic acids and all organic amines) are added to the reactor at one time. Although both steps of polyamide resin synthesis are exothermic reactions, the heat released by the reaction is relatively small and insufficient to maintain the process temperature required for the reaction. External heating is still required to ensure that the reaction, especially the polycondensation reaction, can proceed smoothly at a higher temperature. The selected stirring type can ensure that the material is distributed axially and radially, and the composition of the bottom, middle and top of the reactor is almost the same and the distribution is uniform. Dropwise amine addition is difficult to operate, the process parameters are difficult to control, and the requirements for the degree of automation of the equipment are high. This invention uses all raw materials, including organic amines, to be added to the reactor at one time, which is simple to operate, the process parameters are easy to control, and it is more suitable for industrial production.

[0059] 5. In the first step of the synthesis process of modified polyamide resin in this product - amidation reaction (also known as salt formation reaction), phenylphosphine acid is added as a catalyst, which helps to accelerate the reaction rate of organic acids (including dimer acids and trimeric acids and monoacids in dimer acids, as well as acids with other functional uses) and organic amines (including the main component ethylenediamine and limited components with other functional uses) in the reaction system. The amidation reaction time is shortened by 1.5 hours compared with the currently common production process.

[0060] After adding phenylphosphine to the reaction system, the monoacid, triacid, and a small amount of polyacid components in the raw material dimer acid all participate in the amidation reaction. In particular, most of the monoacid components in the raw material dimer acid are C12-C18 long-chain fatty acids, which have a beneficial effect on the performance indicators of the generated polyamide resin product, such as softening point and anti-gel properties, without the need to add other long-chain fatty acids to improve the performance of the product.

[0061] 6. In the second step of the synthesis process of the modified polyamide resin of this product - the polycondensation reaction - tetrabutyl titanate is added as a polycondensation catalyst. The polycondensation reaction time is shortened by nearly 2 hours compared with the current general production process, and the reaction temperature is reduced by 10℃ compared with the current general production process.

[0062] 7. In the later stage of the polycondensation reaction, before releasing the material after the vacuuming operation, the material is first filtered through a precision filter (with a heat-insulating jacket) to remove solid and mechanical impurities from the reactants. This results in a product with a better appearance (lighter color) and no visually detectable solid and mechanical impurities in the solvent during solubility testing. When applied to ink preparation, this also reduces the impact of solid and mechanical impurities on various quality indicators of the ink.

[0063] 8. To determine whether the first step reaction - amidation reaction - has reached its endpoint, two criteria are used: first, measure the total amount of water released from the water receiver, ensuring that the amount of water reaches 90% of the theoretical value; second, observe the change in the water flowing out of the sight glass connected between the condenser and the water receiver. When the water flowing out of the sight glass changes from a thin stream to droplets and the amount of droplets decreases until almost no water droplets appear.

[0064] 9. Analyze whether the amine value and acid value both meet the process requirements to determine whether the polycondensation reaction has reached its endpoint. This can be used as a basis to guide production.

[0065] 10. The product's storage stability has been improved. Under the specified storage conditions, samples were taken and analyzed after one year and two years of storage, and the main indicators of the product were all qualified.

[0066] 11. The prepared polyamide resin has a light color, high transparency, no irritating odor, a moderate softening point, low acid value and amine value, and is completely soluble in alcohol solvents. The solution is transparent, and no precipitate forms in the solution after two years of storage. Once gelled at low temperatures, it can quickly regain its fluidity at room temperature, posing no harm to humans or the environment. This is environmentally friendly and ensures the safety requirements for food packaging. Detailed Implementation

[0067] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0068] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0069] (I) Use of raw materials

[0070] Industrial grade dimer acid composition and content: dimer acid content 80-85%, trimeric acid and other polyacid content ≤15%, monoacid and other fatty acids, other impurities content ≤5%;

[0071] Lithium diethylene glycol 5-sulfonate, purity ≥99%;

[0072] Industrial acetic acid, main technical requirements: content ≥99%;

[0073] Isobutyric acid, main technical requirements: content ≥ 98%;

[0074] Ricinoleic acid, main technical requirements: content ≥95%;

[0075] Octadiol, main technical requirements: content ≥ 98%;

[0076] Ethylenediamine, main technical requirements: content ≥ 99%;

[0077] Piperazine hexahydrate, main technical requirements: content ≥ 98%.

[0078] Sebacdiamine, main technical requirements: content ≥ 98%;

[0079] Triethanolamine, main technical requirements: content ≥98%;

[0080] catalyst

[0081] Phenylenephosphonic acid, main technical requirements: content ≥ 99%;

[0082] Tetrabutyl titanate, main technical requirements: content ≥98%.

[0083] (II) Main Equipment

[0084] 1. The reactor used for the synthesis and polycondensation reaction is a custom-made 3000ml jacketed round-bottom reactor. The body and top cover are connected by flanges. The opening of the top cover and the orientation of the pipe are similar to the K-type 3000L reactor with stirring used in industrial production. The stirrer used is a screw-ribbon combination stirrer. All materials in contact with the materials are made of 304SST stainless steel. Heating and cooling are automatically controlled. The stirrer motor has frequency conversion control speed.

[0085] 2. The vacuum unit used in the laboratory consists of an oil ring vacuum pump and a three-roots vacuum pump. When running, its ultimate pressure (no load) can reach below 0.1 Pa. The reactor, buffer tank and vacuum unit are connected in sequence.

[0086] (III) Production Operations

[0087] Raw material proportions (molar ratio)

[0088] Organic acid compounds:

[0089] Industrial grade dimer acids (all dimer acids, trimer acids and other polyacids in dimer acids, monoacids and other fatty acids in dimer acids, all converted to molar amounts of dimer acid): Diethylene glycol isophthalate-5-sulfonate lithium: Industrial acetic acid: Isobutyric acid: Ricinoleic acid: Octadionic acid

[0090] =1:0.15-0.36:0.15-0.25:0.15-0.32:0.15-0.28:0.05-0.18,

[0091] The amount of phenylphosphine catalyst added is 0.003%-0.02% of the mass of the dimer acid;

[0092] Amine compounds:

[0093] Ethylenediamine:piperazine hexahydrate:decanediamine:triethanolamine = 1:0.15-1:0.02-0.25; 0.15-0.27;

[0094] The amount of tetrabutyl titanate catalyst added is 0.008%-0.06% of the mass of the dimer acid.

[0095] The molar ratio of organic acid compounds to amine compounds is 1:1.05-1.2, with amine compounds in excess.

[0096] The operation process is as follows:

[0097] 1. Feeding: Weigh the industrial dimer acid, lithium diethylene glycol isophthalate-5-sulfonate, industrial acetic acid, isobutyric acid, ricinoleic acid, octanoic acid, and the catalyst phenylphosphine acid into the reactor through the feed port on the top cover. Close the feed port valve, start the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Sequentially vacuum-pump the weighed ethylenediamine, decanediamine, triethanolamine, and piperazine hexahydrate solution dissolved in hot water into the reactor through the discharge port at the bottom of the reactor. After the material is sucked in, close the discharge port valve. Then open the nitrogen cylinder outlet valve, and then open the feed port valve on the top cover of the reactor to introduce nitrogen gas. When the pressure gauge of the reactor shows a slight positive pressure, purge the gas. Repeat the purging process three times, and then close the nitrogen cylinder outlet valve.

[0098] 2. After all materials for the amidation reaction have been added, stir for 0.5–1 hour, then begin heating the reactor. Raise the reactor temperature to 100–110°C within 15–25 minutes and maintain this temperature for 1–1.5 hours. Next, raise the reactor temperature to 130–150°C and maintain this temperature for 1–1.5 hours. At this point, observe that the water flowing out of the sight glass changes from a thin stream to droplets, with the number of droplets decreasing until almost no more droplets appear. Measure the amount of water released from the water receiver. If the amount of water reaches 90% of the theoretically calculated value, this indicates that the amidation reaction has ended.

[0099] 3. Polycondensation reaction: Add tetrabutyl titanate catalyst to the reactor all at once, continue heating, raise the temperature to 180℃~200℃ within 20~30 minutes, maintain for 1.5~2 hours, raise the temperature again, raise the temperature inside the reactor to 220℃~230℃ within 10~20 minutes, maintain for 0.5~1 hour; after maintaining the temperature within the range of 220℃~230℃, take a sample from the bottom discharge port of the reactor for analysis of amine value and acid value. If both are qualified, vacuum the reactor and start the vacuum unit according to the standard operation. Start timing from when the absolute pressure inside the reactor reaches 150Pa, and vacuum the reactor for 0.5~1 hours. During this process, maintain the temperature inside the reactor at 220℃~230℃.

[0100] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product, which is then sampled for analysis.

[0101] Example 1

[0102] 1. Feeding: Weigh 1250g of industrial dimer acid, 151.4g of lithium diethylene glycol 5-sulfonate, 22.8g of industrial acetic acid, 31.8g of isobutyric acid, 142.4g of ricinoleic acid, 54.2g of octanoic acid, and 0.01g of phenylphosphine catalyst and add them to the reactor through the top cover feed port. Close the feed port valve, start the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Sequentially draw 134.4g of ethylenediamine, 54.2g of decanediamine, 57.3g of triethanolamine, and 195.4g of piperazine hexahydrate dissolved in 750g of hot water into the reactor through the bottom discharge port. After the materials are drawn in, close the discharge port valve, then open the nitrogen cylinder outlet valve, and then open the top cover feed port valve to introduce nitrogen. When the reactor pressure gauge shows a slight positive pressure, vent the gas. Repeat the venting process three times, and then close the nitrogen cylinder outlet valve.

[0103] 2. After all materials for the amidation reaction have been added, stir for 40 minutes, then start heating the reactor. Raise the temperature inside the reactor to 100°C within 15 minutes and maintain it for 1.2 hours. Then raise the temperature inside the reactor to 130°C and maintain it for 1.5 hours. At this point, observe that the water flowing out of the sight glass changes from a thin stream to droplets, and the amount of droplets becomes smaller and smaller until almost no water droplets appear. Weigh the water released from the water receiver; the amount is 875.2 grams (the amount of water has reached more than 90% of the theoretical calculation value), indicating that the amidation reaction is complete.

[0104] 3. Polycondensation reaction: Add tetrabutyl titanate catalyst to the reactor all at once, continue heating, raise the temperature to 180℃ within 20 minutes, maintain it for 100 minutes, then raise the temperature again to 220℃ within 10 minutes, and maintain this temperature for 1 hour; take samples from the bottom discharge port of the reactor for analysis: amine value ≤6mgKOH / g, acid value ≤6mgKOH / g. Then, start the vacuum unit according to the conventional operation, start timing from when the absolute pressure inside the reactor reaches 150Pa, and vacuum the reaction for 1 hour, maintaining the temperature inside the reactor at 220℃ during this process;

[0105] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. The analysis results of the product quality indicators are shown in Table 1-1.

[0106] Table 1-1 Analysis Results of Product Quality Indicators

[0107]

[0108] Instructions for gel recovery time testing: Prepare a 40% polyamide resin solution and place it in a wide-mouth bottle. Cool the solution to the specified temperature and start timing. The timing ends when the solution becomes a non-flowing colloid. This time is the gel time. Place the colloid at room temperature and start timing again. The timing ends when the colloid resumes flow. This time is the gel recovery time.

[0109] The product's storage stability analysis is shown in Table 1-2 (only three indicators were tested: softening point, viscosity, and color).

[0110] Table 1-2 Results of Product Storage Stability Analysis

[0111]

[0112] Example 2

[0113] 1. Feeding: Weigh 1250g of industrial dimer acid, 151.4g of lithium diethylene glycol isophthalate-5-sulfonate, 24.2g of industrial acetic acid, 33.5g of isobutyric acid, 181.3g of ricinoleic acid, 38.7g of octanoic acid, and 0.01g of phenylphosphine catalyst and add them to the reactor through the top cover feed port. Close the feed port valve, turn on the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Weigh 134.4g of ethylenediamine, 38.8g of decanediamine, 57.3g of triethanolamine, and 247.5g of piperazine hexahydrate dissolved in 850g of hot water and then feed them into the reactor through the bottom discharge port in sequence. After the feed is finished, close the discharge port valve, then open the nitrogen cylinder outlet valve, and then open the top cover feed port valve to introduce nitrogen. When the pressure gauge of the reactor shows a slight positive pressure, vent the gas. Repeat the venting process three times, and then close the nitrogen cylinder outlet valve.

[0114] 2. After all materials for the amidation reaction have been added, stir for 50 minutes, then start heating the reactor. Raise the temperature inside the reactor to 110°C within 25 minutes and maintain it for 1.5 hours. Then raise the temperature inside the reactor to 150°C and maintain it for 1 hour. At this point, observe that the water flowing out of the sight glass changes from a thin stream to droplets, and the amount of droplets becomes smaller and smaller until almost no water droplets appear. Weigh the water released from the water receiver; the amount is 991.3 grams (the amount of water has reached more than 90% of the theoretical calculation value), indicating that the amidation reaction is complete.

[0115] 3. Polycondensation reaction: Add 0.15 g of tetrabutyl titanate catalyst to the reactor at once, continue heating, raise the temperature to 200°C within 30 minutes, maintain this temperature for 1.5 hours, raise the temperature again, raise the temperature inside the reactor to 230°C within 15 minutes, and maintain this temperature for 1 hour; take samples from the bottom discharge port of the reactor for analysis: amine value ≤6 mgKOH / g, acid value ≤6 mgKOH / g. Then, start the vacuum unit according to the conventional operation, start timing from when the absolute pressure inside the reactor reaches 150 Pa, and vacuum the reaction for 40 minutes, maintaining the temperature inside the reactor at 230°C during this process;

[0116] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. The analysis results of the product quality indicators are shown in Table 2-1.

[0117] Table 2-1 Analysis Results of Product Quality Indicators

[0118]

[0119] Instructions for gel recovery time testing: Prepare a 40% polyamide resin solution and place it in a wide-mouth bottle. Cool the solution to the specified temperature and start timing. The timing ends when the solution becomes a non-flowing colloid. This time is the gel time. Place the colloid at room temperature and start timing again. The timing ends when the colloid resumes flow. This time is the gel recovery time.

[0120] The product's storage stability analysis is shown in Table 2-2 (only three indicators were tested: softening point, viscosity, and color).

[0121] Table 2-2 Results of Product Storage Stability Analysis

[0122]

[0123] Example 3

[0124] 1. Feeding: Weigh 1250g of industrial dimer acid, 151.4g of lithium diethylene glycol isophthalate-5-sulfonate, 28.2g of industrial acetic acid, 39.4g of isobutyric acid, 144g of ricinoleic acid, 58.1g of octanoic acid, and 0.01g of phenylphosphine catalyst and add them to the reactor through the top cover feed port. Close the feed port valve, start the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Sequentially draw 134.4g of ethylenediamine, 58.1g of decanediamine, 57.3g of triethanolamine, and 230g of piperazine hexahydrate dissolved in 800g of hot water into the reactor through the bottom discharge port. After the materials are drawn in, close the discharge port valve, then open the nitrogen cylinder outlet valve, and then open the top cover feed port valve to introduce nitrogen. When the reactor pressure gauge shows a slight positive pressure, vent the gas. Repeat the venting process three times, and then close the nitrogen cylinder outlet valve.

[0125] 2. After all materials for the amidation reaction have been added, stir for 1 hour and then start heating the reactor. Raise the temperature inside the reactor to 105°C within 25 minutes and maintain it for 0.5 hours. Then raise the temperature inside the reactor to 135°C and maintain it for 1.5 hours. At this time, observe that the water flowing out of the sight glass changes from a thin stream to droplets, and the amount of droplets becomes less and less until almost no water droplets appear. Weigh the water released from the water receiver and it is 943.7 grams (the amount of water has reached more than 90% of the theoretical calculation value), and the amidation reaction is complete.

[0126] 3. Polycondensation reaction: Add tetrabutyl titanate catalyst to the reactor all at once, continue heating, raise the temperature to 190℃ within 30 minutes, maintain for 2 hours, raise the temperature again, raise the temperature inside the reactor to 225℃ within 20 minutes, and maintain this temperature for 1 hour; take samples from the bottom discharge port of the reactor for analysis: amine value ≤6mgKOH / g, acid value ≤6mgKOH / g. Then, start the vacuum unit according to the conventional operation, start timing from when the absolute pressure inside the reactor reaches 150Pa, and vacuum the reaction for 1 hour, maintaining the temperature inside the reactor at 225℃ during this process;

[0127] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. The analysis results of the product quality indicators are shown in Table 3-1.

[0128] Table 3-1 Analysis Results of Product Quality Indicators

[0129]

[0130] Instructions for gel recovery time testing: Prepare a 40% polyamide resin solution and place it in a wide-mouth bottle. Cool the solution to the specified temperature and start timing. The timing ends when the solution becomes a non-flowing colloid. This time is the gel time. Place the colloid at room temperature and start timing again. The timing ends when the colloid resumes flow. This time is the gel recovery time.

[0131] The product's storage stability analysis is shown in Table 3-2 (only three indicators were tested: softening point, viscosity, and color).

[0132] Table 3-2 Results of Product Storage Stability Analysis

[0133]

[0134] Example 4

[0135] 1. Feeding: Weigh 1250g of industrial dimer acid, 151.4g of lithium diethylene glycol isophthalate-5-sulfonate, 29.5g of industrial acetic acid, 39.4g of isobutyric acid, 161.8g of ricinoleic acid, 46.4g of octanoic acid, and 0.02g of phenylphosphine catalyst and add them to the reactor through the top cover feed port. Close the feed port valve, start the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Sequentially draw 134.4g of ethylenediamine, 46.4g of decanediamine, 57.3g of triethanolamine, and 230g of piperazine hexahydrate dissolved in 800g of hot water into the reactor through the bottom discharge port. After the materials are drawn in, close the discharge port valve, then open the nitrogen cylinder outlet valve, and then open the top cover feed port valve to introduce nitrogen. When the reactor pressure gauge shows a slight positive pressure, vent the gas. Repeat the venting process three times, and then close the nitrogen cylinder outlet valve.

[0136] 2. After all materials for the amidation reaction have been added, stir for 40 minutes, then begin heating the reactor. Raise the reactor temperature to 110°C within 125 minutes and maintain it for 80 minutes. Then raise the reactor temperature to 130°C and maintain it for 80 minutes. At this point, observe that the water flowing out of the sight glass changes from a thin stream to droplets, and the number of droplets decreases until almost no water droplets appear. Weigh the water released from the water receiver; the amount is 944.5 grams (the amount of water has reached more than 90% of the theoretical calculation value), indicating that the amidation reaction is complete.

[0137] 3. Polycondensation reaction: Tetrabutyl titanate catalyst is added to the reactor all at once. The temperature is continuously increased to 200℃ within 25 minutes and maintained for 1.52 hours. The temperature is increased again to 225℃ within 120 minutes and maintained at this temperature for 50 minutes. Samples are taken from the bottom discharge port of the reactor for analysis. The amine value is ≤6mgKOH / g and the acid value is ≤6mgKOH / g. Then, the vacuum unit is turned on according to the conventional operation. The timer starts from when the absolute pressure inside the reactor reaches 150Pa and the vacuum reaction is carried out for 50 minutes. During this process, the temperature inside the reactor is maintained at 225℃.

[0138] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. The analysis results of the product quality indicators are shown in Table 4-1.

[0139] Table 4-1 Analysis Results of Product Quality Indicators

[0140]

[0141] Instructions for gel recovery time testing: Prepare a 40% polyamide resin solution and place it in a wide-mouth bottle. Cool the solution to the specified temperature and start timing. The timing ends when the solution becomes a non-flowing colloid. This time is the gel time. Place the colloid at room temperature and start timing again. The timing ends when the colloid resumes flow. This time is the gel recovery time.

[0142] The product's storage stability analysis is shown in Table 4-2 (only three indicators were tested: softening point, viscosity, and color).

[0143] Table 4-2 Results of Product Storage Stability Analysis

[0144]

[0145] Example 5

[0146] 1. Feeding: Weigh 1250g of industrial dimer acid, 151.4g of lithium diethylene glycol 5-sulfonate, 32.2g of industrial acetic acid, 61.1g of isobutyric acid, 1110g of ricinoleic acid, 31g of octanoic acid, and 0.03g of phenylphosphine catalyst and add them to the reactor through the top cover feed port. Close the feed port valve, start the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Weigh 134.4g of ethylenediamine, 93.4g of decanediamine, 57.3g of triethanolamine, and 416.8g of piperazine hexahydrate dissolved in 1000g of hot water and sequentially draw them into the reactor through the bottom discharge port. After the materials are drawn in, close the discharge port valve, then open the nitrogen cylinder outlet valve, and then open the top cover feed port valve to introduce nitrogen. When the reactor pressure gauge shows a slight positive pressure, vent the gas. Repeat the venting process three times, and then close the nitrogen cylinder outlet valve.

[0147] 2. After all materials for the amidation reaction have been added, stir for 0.5 hours and then start heating the reactor. Raise the temperature inside the reactor to 1110℃ within 25 minutes and maintain it for 1.5 hours. Then raise the temperature inside the reactor to 140℃ and maintain it for 80 minutes. At this time, observe that the water flowing out of the sight glass changes from a thin stream to droplets, and the amount of droplets becomes smaller and smaller until almost no water droplets appear. Weigh the water released from the water receiver and it is 1222.5 grams (the amount of water has reached more than 90% of the theoretical calculation value). The amidation reaction is complete.

[0148] 3. Polycondensation reaction: Add tetrabutyl titanate catalyst to the reactor all at once, continue heating, raise the temperature to 200℃ within 30 minutes, maintain it for 1.5 hours, raise the temperature again, raise the temperature inside the reactor to 230℃ within 20 minutes, and maintain this temperature for 1 hour; after the holding time is completed, take a sample from the bottom discharge port of the reactor for analysis. The amine value is ≤6mgKO H / g and the acid value is ≤6mgKOH / g. Then, start the vacuum unit according to the conventional operation. Start timing from when the absolute pressure inside the reactor reaches 150Pa, and vacuum the reaction for 50 minutes. During this process, maintain the temperature inside the reactor at 230℃.

[0149] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. The analysis results of the product quality indicators are shown in Table 5-1.

[0150] Table 5-1 Analysis Results of Product Quality Indicators

[0151]

[0152] Instructions for gel recovery time testing: Prepare a 40% polyamide resin solution and place it in a wide-mouth bottle. Cool the solution to the specified temperature and start timing. The timing ends when the solution becomes a non-flowing colloid. This time is the gel time. Place the colloid at room temperature and start timing again. The timing ends when the colloid resumes flow. This time is the gel recovery time.

[0153] The product's storage stability analysis is shown in Table 5-2 (only three indicators were tested: softening point, viscosity, and color).

[0154] Table 5-2 Results of Product Storage Stability Analysis

[0155]

[0156] The stability of the 40% resin solution of the prepared sample (refer to the relevant standard clause of QB / T 4752-2014) was observed, and the comparison results are shown in Table 6.

[0157] Table 6. Comparison of the stability of the 40% resin solution of the prepared samples with domestic and foreign sample solutions.

[0158] Example 1 1 1 1 4 Example 2 1 1 1 4 Example 3 1 1 1 4 Example 4 1 1 1 4 Example 5 1 1 1 4 An enterprise in Anhui 1 2 2 3 A company in Shandong 1 2 2 3 A company in Jiangsu 1 2 3 3 Imported from Japan 1 1 1 1 German imports 1 1 1 1

[0159] Explanation of the meaning of the numbers: 1 - The solution is clear and transparent; 2 - The solution has fine precipitates floating without sediment; 3 - The solution is turbid and has sediment; 4 - The solution changes color.

[0160] Other notes: The samples from the three companies in Anhui, Shandong, and Jiangsu are all dimer acid type polyamide resins, used as binders for ink preparation.

[0161] Comparative Example 1

[0162] The material ratio and operating parameters are the same as in Example 4, except that the amount of "lithium diethylene glycol isophthalate-5-sulfonate" is changed to "sodium diethylene glycol isophthalate-5-sulfonate". The amount of "sodium diethylene glycol isophthalate-5-sulfonate" is equimolar with the amount of "lithium diethylene glycol isophthalate-5-sulfonate", which is 158.5 grams.

[0163] The results of the analysis of the quality indicators of the prepared products are shown in Table 7-1.

[0164] Table 7-1 Analysis Results of Product Quality Indicators

[0165]

[0166] As shown in Table 7-1, the resin prepared using sodium diethylene glycol isophthalate-5-sulfonate meets all the requirements for test indicators, but its freeze-thaw performance is not as good as that of the resin prepared using lithium diethylene glycol isophthalate-5-sulfonate. This is mainly because lithium atoms have a smaller diameter than sodium atoms, resulting in less steric hindrance in the resin structure chain, greater flexibility, and thus a lower freezing point, which is 2°C lower than that of the resin prepared using sodium diethylene glycol isophthalate-5-sulfonate.

[0167] The product's storage stability analysis is shown in Table 7-2 (only three indicators were tested: softening point, viscosity, and color).

[0168] Table 7-2 Results of Product Storage Stability Analysis

[0169]

[0170]

[0171] The solubility of the prepared sample in a 40% resin solution (refer to the corresponding standard clause of QB / T 4752-2014) was compared, and the comparison results are shown in Table 7-3.

[0172] Table 7-3 Comparison of the solubility of 40% resin solution in the prepared samples

[0173]

[0174] Comparative tests under the same operating conditions, as shown in Table 7-3, reveal that the resin prepared using lithium diethylene glycol isophthalate-5-sulfonate dissolves faster and exhibits significantly better solution stability than the resin prepared using sodium diethylene glycol isophthalate-5-sulfonate. This is directly related to the molecular structure and block composition of the two resins. The reason for this may be that, under the same synthesis conditions, sodium-containing polyamide resins with the same structure possess higher cohesive energy, crystallinity, and chemical stability than lithium-containing resins. Since polyamide resins are polymers that fully extend their molecular chains after complete dissolution in a liquid solution, and sodium ions have a larger ionic radius and relatively greater steric hindrance than lithium ions, their dissolution rate is relatively slower, according to the general rules of polymer dissolution.

[0175] The products obtained in the embodiments of this application are mixtures of various block polymers, and typical ones include the following structures:

[0176] Block polymer 1 structure:

[0177]

[0178] Wherein, D is the structure of a dimer acid excluding the carboxyl group, or the structure of a dicarboxylic acid excluding the carboxyl group;

[0179] R is a fatty chain, that is, a fatty chain that connects to an amino group;

[0180] R' stands for alkyl, monocarboxylic fatty acid.

[0181] Block polymer 2 structure:

[0182]

[0183] Wherein, D is the structure in the molecule of a dimer acid other than the carboxyl group, or the structure in the molecule of a dicarboxylic acid other than the carboxyl group;

[0184] R is a fatty chain, that is, a fatty chain that connects to an amino group;

[0185] R' is an alkyl group, a monocarboxylic fatty acid;

[0186] A stands for piperazine.

[0187] The addition of lithium diethylene glycol isophthalate-5-sulfonate as a modifier yields a block polymer 3 structure:

[0188]

[0189] Among them, R is a fatty chain, that is, a fatty chain that connects to an amino group;

[0190] R' stands for alkyl, monocarboxylic fatty acid.

[0191] Comparative Example 2

[0192] The material ratios and operating parameters are the same as in Example 4, except that the catalyst phenylphosphine is no longer added to the material ratio. The specific operation is as follows:

[0193] 1. Feeding: Weigh 1250g of polyacid, 151.4g of lithium diethylene glycol 5-sulfonate, 29.5g of industrial acetic acid, 39.4g of isobutyric acid, 161.8g of ricinoleic acid, and 46.4g of octanoic acid and feed into the reactor through the top feed port. Close the feed port valve, start the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Weigh 134.4g of ethylenediamine, 46.4g of decanediamine, 57.3g of triethanolamine, and 230g of piperazine hexahydrate dissolved in 800g of hot water and feed into the reactor through the bottom discharge port in sequence. After the feed is finished, close the discharge port valve, then open the nitrogen cylinder outlet valve, and then open the top feed port valve of the reactor to introduce nitrogen. When the pressure gauge of the reactor shows a slight positive pressure, purge the gas. Repeat the purging process three times, and then close the nitrogen cylinder outlet valve.

[0194] 2. After all materials for the amidation reaction have been added, the reactor is stirred for 40 minutes, then heated to 110°C within 125 minutes and maintained for 80 minutes. Next, the reactor temperature is raised to 130°C and maintained for 80 minutes. At this point, a significant amount of water is observed flowing out of the sight glass; the amount of water released from the water receiver is measured to be 673 grams. The reaction continues for another 80 minutes, at which point the flow rate of water out of the sight glass decreases; a second weighing shows 153.6 grams of water released from the water receiver. The reaction continues for approximately 60 minutes, at which point the flow rate of water out of the sight glass decreases further; a third weighing shows 106.1 grams of water released from the water receiver (total water output 932.7 grams). The amidation reaction can be considered complete.

[0195] 3. Polycondensation reaction: Tetrabutyl titanate catalyst is added to the reactor all at once. The temperature is continuously increased to 200℃ within 25 minutes and maintained for 1.52 hours. The temperature is increased again to 225℃ within 120 minutes and maintained at this temperature for 50 minutes. Samples are taken from the bottom discharge port of the reactor for analysis. The amine value is ≤6mgKOH / g and the acid value is ≤6mgKOH / g. Then, the vacuum unit is turned on according to the conventional operation. The timer starts from when the absolute pressure inside the reactor reaches 150Pa and the vacuum reaction is carried out for 50 minutes. During this process, the temperature inside the reactor is maintained at 225℃.

[0196] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. The analysis results of the product quality indicators are shown in Table 8.

[0197] Table 8. Analysis Results of Product Quality Indicators

[0198]

[0199]

[0200] As can be seen from the operation process, without using a catalyst, the first step of amidation reaction takes 150 minutes longer than with a catalyst. Although the quality indicators of the prepared product are qualified, the freezing point is higher than that of the product prepared with a catalyst.

[0201] Comparative Example 3

[0202] The material ratios and operating parameters are the same as in Example 4, except that phosphoric acid is used instead of the phenylphosphine catalyst used in this application. The specific operation is as follows:

[0203] 1. Feeding: Weigh 1250g of polyacid, 151.4g of lithium diethylene glycol 5-sulfonate, 29.5g of industrial acetic acid, 39.4g of isobutyric acid, 161.8g of ricinoleic acid, 46.4g of octanoic acid, and 0.1g of phosphoric acid and add them to the reactor through the feed port on the top cover of the reactor. Close the feed port valve, turn on the reactor agitator, and turn on the oil ring vacuum pump in the combined vacuum unit. Weigh 134.4g of ethylenediamine, 46.4g of decanediamine, 57.3g of triethanolamine, and 230g of piperazine hexahydrate dissolved in 800g of hot water and then feed them into the reactor through the discharge port at the bottom of the reactor. After the feed is finished, close the discharge port valve, then open the nitrogen cylinder outlet valve, and then open the feed port valve on the top cover of the reactor to introduce nitrogen. When the pressure gauge of the reactor shows a slight positive pressure, vent the gas. Repeat the venting process three times and then close the nitrogen cylinder outlet valve.

[0204] 2. After all materials for the amidation reaction have been added, stir for 40 minutes, then start heating the reactor. Raise the reactor temperature to 110°C within 125 minutes and maintain it for 80 minutes. Then raise the reactor temperature to 130°C and maintain it for 80 minutes. At this point, it is observed that there is still a lot of water flowing out of the sight glass. After reacting for another 160 minutes, it is observed that the flow rate of water flowing out of the sight glass gradually decreases. After continuing the reaction for 10 minutes, the amount of water released from the water receiver is weighed and found to be 936.2 grams. The amidation reaction can be considered complete.

[0205] 3. Polycondensation reaction: Tetrabutyl titanate catalyst is added to the reactor all at once. The temperature is continuously increased to 200℃ within 25 minutes and maintained for 1.52 hours. The temperature is increased again to 225℃ within 120 minutes and maintained at this temperature for 50 minutes. Samples are taken from the bottom discharge port of the reactor for analysis. The amine value is ≤6mgKOH / g and the acid value is ≤6mgKOH / g. Then, the vacuum unit is turned on according to the conventional operation. The timer starts from when the absolute pressure inside the reactor reaches 150Pa and the vacuum reaction is carried out for 50 minutes. During this process, the temperature inside the reactor is maintained at 225℃.

[0206] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. The analysis results of the product quality indicators are shown in Table 9.

[0207] Table 9 shows the analysis results of the product quality indicators obtained.

[0208]

[0209] The operational process shows that using phosphoric acid as a catalyst instead of phenylphosphine increases the first-step amidation reaction time by 160 minutes compared to using phenylphosphine as a catalyst. Furthermore, the acid value and amine value of the prepared product fail to meet quality standards. This is mainly because the organic acid and amine compounds in the reaction system do not react completely. The catalytic activity of phosphoric acid is also inferior to that of phenylphosphine. It can also be attributed to the mismatch between using phosphoric acid as a catalyst and the other raw materials and reaction conditions. However, the freezing point of the product prepared using a catalyst is higher than that of the product prepared using a catalyst.

[0210] Comparative Example 4

[0211] The material ratios and operating parameters are the same as in Example 2, except that dibutyltin laurate is used instead of tetrabutyl titanate, the catalyst used in this application. The specific operation is as follows:

[0212] 1. Adding ingredients

[0213] The operation is the same as in Example 2.

[0214] 2. Amide reaction

[0215] The operation is the same as in Example 2.

[0216] 3. For the polycondensation reaction, add 0.15 g of dibutyltin lauryl laurate catalyst to the reactor at once, continue heating, raise the temperature to 200°C within 30 minutes, maintain this temperature for 1.5 hours, raise the temperature again, raise the temperature inside the reactor to 230°C within 15 minutes, and maintain this temperature for 1 hour. Take samples from the bottom discharge port of the reactor for analysis. The amine value should be ≤6 mgKOH / g and the acid value should be ≤6 mgKOH / g. Then, start the vacuum unit according to the conventional operation. Start timing from when the absolute pressure inside the reactor reaches 150 Pa, and vacuum the reaction for 40 minutes. During this process, maintain the temperature inside the reactor at 230°C.

[0217] 4. After filtration and vacuuming, nitrogen is used to pressurize the material from the reactor into a precision filter (with an insulation jacket) for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen and cooled to 160°C. The material is then discharged to obtain the finished product. Samples are taken for analysis. The results of the product quality index analysis are shown in Table 10-1.

[0218] Table 10 shows the analysis results of the product quality indicators obtained.

[0219]

[0220] As shown in Table 10, the product prepared using the catalyst dibutyltin lauryl laurate has unsatisfactory color, and its softening point and viscosity are lower than those of the product prepared using the catalyst tetrabutyl titanate. The freezing point is higher than that of Example 2. The unsatisfactory color is mainly due to the nature of the catalyst dibutyltin lauryl laurate itself. The thermal stability of metallic tin is not enhanced, and prolonged heating leads to degradation reactions, causing the resin to turn yellow and produce thermal decomposition products, thus reducing the product's properties (such as viscosity).

[0221] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing an alcohol-soluble modified polyamide resin, characterized in that, The mixture is prepared by reacting organic acids and amine compounds. The organic acids include industrial-grade dimer acid, lithium diethylene glycol isophthalate-5-sulfonate, industrial-grade acetic acid, isobutyric acid, ricinoleic acid, and octanoic acid. The amine compounds include ethylenediamine, piperazine, decanediamine, and triethanolamine. The molar ratio of the organic acid to the amine compound is 1:1.05-1.

2. The molar ratio of industrial-grade dimer acid, lithium diethylene glycol isophthalate-5-sulfonate, industrial-grade acetic acid, isobutyric acid, ricinoleic acid, and octanoic acid in the organic acid is 1:0.15-0.36:0.15-0.25:0.15-0.32:0.15-0.28:0.05-0.

18. In industrial dimer acids, all dimer acids, trimer acids and other polyacids in dimer acids, monoacids and other fatty acids in dimer acids are converted into moles of dimer acids. The industrial-grade dimer acid contains 80-85% dimer acid, ≤15% trimeric acid and other polyacids, and ≤5% monoacids, other fatty acids, and other impurities. The molar ratio of ethylenediamine, piperazine, decanediamine, and triethanolamine in the amine compound is 1:0.15-1:0.02-0.25:0.15-0.

27. The first step of the preparation method, the amidation reaction, uses phenylphosphine as a catalyst, and the amount added is 0.003%-0.02% of the mass of the industrial-grade dimer acid. The second step of the preparation method, the polycondensation reaction, uses tetrabutyl titanate as a catalyst, and the amount added is 0.008%-0.06% of the mass of the industrial grade dimer acid.

2. The method for preparing an alcohol-soluble modified polyamide resin according to claim 1, characterized in that, Includes the following steps: Step 1, Feeding: Add organic acid and catalyst phenylphosphine to the reactor and stir. Use vacuum to draw amine compounds into the reactor from the bottom. After feeding is complete, introduce nitrogen gas. When the pressure gauge of the reactor shows a slight positive pressure, vent the gas and turn off the nitrogen gas. Step 2, amidation reaction: After all materials have been added, heat the mixture to react. Step 3, Polycondensation reaction: Add the catalyst tetrabutyl titanate to the reactor all at once, and continue to heat the reactor for further reaction; Step 4: Filter and discharge.

3. The method for preparing an alcohol-soluble modified polyamide resin according to claim 2, characterized in that, Step 2, the amidation reaction, adopts a gradient temperature program. After all materials are added, the reactor is stirred for 0.5 to 1 hour and then heated. The temperature inside the reactor is raised to 100°C to 110°C within 15 to 25 minutes and maintained for 1 to 1.5 hours. Then, the temperature inside the reactor is raised to 130°C to 150°C and maintained for 1 to 1.5 hours.

4. The method for preparing an alcohol-soluble modified polyamide resin according to claim 2, characterized in that, Step 3, the polycondensation reaction, adopts a gradient temperature program. The catalyst tetrabutyl titanate is added to the reactor all at once, and the temperature is continued to rise to 180℃~200℃ within 20~30 minutes. After holding for 1.5~2 hours, the temperature is raised again to 220℃~230℃ within 10~20 minutes and held for 0.5~1 hour. The temperature is then maintained within the range of 220℃~230℃.

5. The method for preparing an alcohol-soluble modified polyamide resin according to claim 2, characterized in that, Includes the following steps: Step 1, Feeding: Weigh the industrial dimer acid, lithium diethylene glycol isophthalate-5-sulfonate, industrial acetic acid, isobutyric acid, ricinoleic acid, octanoic acid, and catalyst phenylphosphine acid into the reactor through the feed port on the top cover. Turn on the reactor stirring. Weigh the ethylenediamine, decanediamine, triethanolamine, and piperazine hexahydrate solution dissolved in hot water into the reactor through the discharge port at the bottom of the reactor in sequence using vacuum suction. After the suction is completed, close the discharge port valve, then open the feed port valve on the top cover of the reactor and introduce nitrogen gas. When the pressure gauge of the reactor shows a slight positive pressure, vent the gas. Repeat the venting process three times and close the nitrogen cylinder outlet valve. Step 2, amidation reaction: After all materials have been added, stir for 0.5 to 1 hour and then start heating the reactor. Raise the temperature inside the reactor to 100℃ to 110℃ within 15 to 25 minutes and maintain it for 1 to 1.5 hours. Then raise the temperature inside the reactor to 130℃ to 150℃ and maintain it for 1 to 1.5 hours. At this time, observe that the water flowing out of the sight glass changes from a thin stream to a droplet, and the amount of droplets becomes less and less until almost no water droplets appear. Measure the amount of water released from the water receiver. If the amount of water reaches 90% of the theoretically calculated value, it indicates that the amidation reaction has ended. Step 3, Polycondensation Reaction: Add the catalyst tetrabutyl titanate to the reactor all at once, continue heating, raise the temperature to 180℃~200℃ within 20~30 minutes, maintain it for 1.5~2 hours, raise the temperature again, raise the temperature inside the reactor to 220℃~230℃ within 10~20 minutes, maintain it for 0.5~1 hour; after maintaining the temperature within the range of 220℃~230℃, take a sample from the bottom discharge port of the reactor for analysis. If the amine value and acid value are both qualified, vacuum the reactor. Start the vacuum unit according to the standard operation. Start timing from the absolute pressure inside the reactor reaching 150Pa, and vacuum the reactor for 0.5~1 hour. During this process, maintain the temperature inside the reactor at 220℃~230℃. Step 4, Filtration and Discharge: After vacuuming, nitrogen is used to press the material from the reactor into a precision filter with an insulated jacket for filtration. The filtered product is placed in a receiving tank that has been purged with nitrogen, cooled to 160°C, discharged, and the finished product is obtained. Samples are taken for analysis.

Citation Information

Patent Citations

  • Method for preparing polyamide resin used for water color ink

    CN101613472B

  • Alcohol-soluble copolyamide and preparation method thereof

    CN103113577A

  • Preparation method of transparent dimer acid type polyamide resin

    CN103554485A

  • A method for preparing an alcohol-soluble dimer acid type polyamide resin

    CN103554486B

  • Preparation method of environment-friendly high-hardness alcohol-soluble polyamide resin

    CN104788671A